DAMPAK KEBIJAKAN TARIF DAN NON-TARIF TERBADAP PERMINTAAN DAN DAYA SAING TUNA INDONESIA DI PASAR UNI EROPA, AMERIKA DAN JEPANG - Ratih Wijayanti; Irham Irham; Suhatmini Hardyastuti (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2011)
The objective of this study is to analyse the impact of implementation tariff and non-tariff policy also the other factors on demand and competitiveness Indonesia's tuna commodity. Panel data was implemented in this research because beside used anually time series data during the period 1983-2008 also used cross section data which describe the demand and competitiveness condition of Indonesia's tuna commodity in three major market. Equation models in this research were estimated with Generalized Least Square (GLS) method withfzxed effect to analyse all of demand and competitiveness of export tuna in three major market and Ordinary Least Square (OLS) method to analyse demand and competitiveness of export tuna in each market. Meanwhile the competitiveness of tuna is measured using Revealed Comparatif Advantage (RCA) index. The results show that export price in European union and shrimp price in Japan are main factors the demand of Indonesia's tuna export in three major market. The change of Gross Domestic Product (GDP) Japan has not been influenced the demand of Indonesia's tuna export to these country because Japan's import of fishery product from Indonesia has been donefrequently and Indonesia's market share is very high. Export tuna from Indonesia is competing with export tuna from Thailand in European and Japan market while with export tuna from Philippines in USA market. Tariff policy more reduce and didn't influenced on demand and competitiveness. Thisfinding were confirmed by significancy which more little than non-tariff policy.Penelitian ini bertujuan untuk mengetahui dampak penerapan kebijakan tarif 'dan non-tarif serta beberapa faktor lainnya terhadap permintaan dan daya saing tuna Indonesia. Data dalam penelitian ini dianalisis menggunakan data panel karena selain menggunakan data runtut waktu (1983-2008) juga menggunakan data silang yang menggambarkan kondisi permintaan dan daya saing tuna di ketiga pasar yaitu Uni Eropa, Amerika dan Jepang. Model persamaan dalam penelitian ini diestimasi dengan metode data panel (Generalized Least Square/ GLS dengan efek tetap) untuk menggambarkan seluruh permintaan dan daya saing ekspor tuna ke tiga pasar dan metode Ordinary Least Square (OLS) untuk menggambarkan kondisi permintaan dan daya saing tuna di masing-masing pasar. Pengukuran daya saing tuna dengan menggunakan indeks Revealed Comparatif Advantage (RCA). Hasil analisis menunjukkan bahwa harga ekspor di Uni .Eropa dan harga udang di Jepang merupakan penentu utama permintaan tuna Indonesia di pasar produktif. Impor perikanan Jepang akan produk tuna dari Indonesia yang sudah rutin dilakukan dan besamya pangsa pasar tuna Indonesia di Jepang menyebabkan perubahan pendapatan nasional (GDP masyarakat Jepang) tidak mempengaruhi permintaan tuna Indonesia ke negara tersebut. Indonesia bersaing dengan Thailand di pasar Uni Eropa dan Jepang serta bersaing dengan Filipina di pasar Amerika. Kebijakan tarif semakin tidak berpengaruh terhadap permintaan dan daya saing tuna Indonesia ke pasar produktif yang dibuktikan dengan nilai signifIkansi yang lebih keeil dibandingkan kebijakan non-tarif yang diberlakukan.